Book Review: The First Muslims History and Memory - Muhammad Bahrul Ulum (University of Jember, 2017)
This is one of remarkably few recent books devoted to the Islamic theoretical conversation of constitutional law, by considering the genesis of polity within the Muslim community through historical, political, theological, and legal perspectives. The book provides the contentious concept of jihad and Islamic state which is perceived as the early Muslims’ legacy in this contemporary world. Specifically, it opens a window into the way of understanding the Muslim history by contesting Muhammad’s tolerant polity and the current extremism notion attached to Islam. Beginning the chapter, Asma Afsaruddin, an associate professor at the University of Notre Dame, presents an account of the dawn of Islam brought by the Prophet Muhammad. She takes the lifetime of Muhammad into an account of how the early Muslim community would be shaped from the age of ignorance (Al-Jahiliyya). The term Al-Jahiliyya refers to the time of recklessness and disregard for certain moral, spiritual, and social values revered by Muslims and other righteous people.